The Challenges of Islamic Literacy of Madrasah Ibtidaiyah Students From the Perspective of the Study of Islamic Education Philosophy - Nasep, Moh; Permana Sari, Dini (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: This study aims to analyze the challenges of Islamic literacy among Madrasah Ibtidaiyah (MI) students from the perspective of Islamic educational philosophy, emphasizing the interrelation between basic literacy skills, learning processes, and the support provided by family and school environments. Methodology: Employing an explanatory sequential mixed-method design, the quantitative phase involved administering Islamic literacy tests and questionnaires to 127 students in grades 5 and 6, followed by qualitative data collection through interviews, observations, and documentation to deepen the analysis. Main Findings: The findings indicate that students’ Islamic literacy levels fall within the moderate category, with particularly low performance in reading hijaiyah letters and understanding the meanings of Islamic texts. Additional inhibiting factors include the predominance of lecture-based teaching, limited use of varied learning media, low student reading interest, and insufficient literacy facilities both at home and in the madrasah. Parental support was also found to be limited, resulting in inconsistent literacy habits. From the standpoint of Islamic educational philosophy, these conditions reflect a significant gap between the ideal goal of forming the insan kamil and the actual literacy competencies of students, which have not yet been integrated across cognitive, spiritual, and moral dimensions. Novelty/Originality of this study: This study underscores the need to strengthen a comprehensive Islamic literacy ecosystem by enhancing pedagogical strategies, improving literacy facilities, and fostering family–school collaboration to support the formation of Islamic character from an early age.